Studies in law, politics and society. Vol. 53 - Sarat, Austin (Bingley, U.K. : Emerald, 2010)
This volume of Studies in Law, Politics, and Society includes a special collection of chapters entitled 'Making Sense of the Past: When History Meets Law.' The articles in this symposium consider the ways in which history has shaped law and how we make sense of past events. In addition, the volume contains general articles that explore pressing legal issues such as the prison boom, First Amendment controversies, and the work of cause lawyers. As has long been the tradition with this series, Volume 53 illustrates the vibrancy of interdisciplinary legal scholarship throughout.
A 'switch in time' beyond the nine : historical memory and the constitutional revolution of the 1930s / John W. Wertheimer -- Making sense of Blackstone's puzzle : why forbid defense counsel? / Thomas P. Gallanis -- Visions of Cádiz : the Constitution of 1812 in historical and constitutional thought / M. C. Mirow -- Theorizing the first amendment : from Roger Williams to Larry Flynt / H. N. Hirsch -- The political analysis of mass incarceration / Peter Hovde -- Cause lawyering for American Indian voting rights : comparing public and private attorneys / Susan M. Olson.
Print version record
Keywords: Law -- Government -- General; Law -- General; Law -- Legal History; Law & society; Legal system: general; Sociological jurisprudence; Law -- Political aspects